Pittsburgh Meeting of Coal Division Proves "Lucky Seventh" Fuels Conference in Both Attendance and Interest - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1943)
T. E. PURCELL, general chairman . of the local committee, opened the seventh meeting of the Fuels Division A.S.M.E. and the Coal Division A.I.M.E., at the William Penn Hotel, Pittsburgh, Oct. 28-29, by introducing Harry M. Moses, president, H. C. Frick Coke Co., who welcomed the 500 registrants to "our town." Mr. Moses, in his brief talk, declared that in the postwar period each of the new centers must have a reason for existence. Pittsburgh, he said, has no iron ore, or bauxite, and limestone is scattered and not near by; but Pittsburgh does have low-cost fuel within reasonable distance. Its problem is the economical utilization of the low-cost fuels that remain, as the high-quality fuels are gone. Mr. Moses expressed confidence in this group in the solution of the problem and looked forward to what they would do. Harold V. Coes, the first A.S.M.E. president to attend one of these conferences, responded. He thoroughly believed in these joint meetings - in the cross-fertilization of ideas. Each Division learns from the other. Mr. Purcell then turned the meeting over to J. E. Tobey who presided over the coal research session that followed.